O complexo holosericeus de ommatius wiedemann no Brasil: Nova espécie e primeiro registro do grupo ampliatus para o país e novos registros para o grupo holosericeus (Diptera, Asilidae) - Vieira, Rodrigo; Bravo, Freddy; Rafael, José Albertino (Revista Brasileira de Entomologia, 2011)
The holosericeus complex of Ommatius Wiedemann in Brazil: a new species and first record of the ampliatus group for the country and new records for the holosericeus group (Diptera, Asilidae). In this paper a new species of Ommatius Wiedemann, 1821 belonging to the ampliatus group is described from the Amazonas state. Furthermore, new records, taxonomic variations, illustrations and description of male and female terminalia are provided for the species of the holosericeus group.
Keywords: Asilidae; Diptera; Ommatiinae; Ommatius; Terminalia; Asilidae; Diptera; Ommatiinae; Ommatius; Terminalia